New Instruments for Impact Assessment: study of an academic library - Melo, Luiza Baptista; Cruz, Célia; Sá, Isabel (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
This study presents a review of new instruments for the impact assessment of libraries and a case study of the evaluation impact of the Library of the Faculty of Science, University of Porto (FCUP), from the students’ point of view. We conducted a mixed methods research, i.e., which includes both qualitative data, to describe characteristics, in particular human actions, and quantitative data, represented by numbers that indicate exact amounts which can be statistically manipulated. Applying International Standard ISO16439:2014 (E) - Information and documentation - Methods and procedures for assessing the impact of libraries, we collected, 20 opinion texts from students of different nationalities, published in «Notícias da Biblioteca», from January 2013 to December 2014 and have conducted seven interviews.